Application of the Dijkstra method in finding the shortest route for hospitals in Kabupaten Tegal - Gunawan Gunawan; Wresti Andriani; Khadziqul Humam Munfi (Institute of Computer Science (IOCS), 2023)
Health services are one of the most critical aspects of human life. Getting medical care quickly and efficiently can be a determining factor in saving a person's life in an emergency. In this article, we will review the application of the Dijkstra Method in finding the shortest route to Mitra Siaga hospitals in Kabupaten Tegal. This article is expected to contribute to understanding and developing a more efficient transportation system in Kabupaten Tegal, focusing on health services. Dijkstra algorithm for determining the shortest route. Dijkstra's algorithm is an algorithm that intends to find the shortest path on a graph. The principle of the Dijkstra Algorithm is searching for two passes with the most negligible weight. Based on the results of testing 10 times, the accuracy of this application is 100%. In this study, limited to the initial location tested, this application has not used the current location at its initial location. For the development of this application, you can use the current location at the initial location so that this application runs optimally